Migrant families with disabled children: Parent perspectives - Egilson, Snæfríður Þóra; Skaptadóttir, Unnur Dís; Ottósdóttir, Guðbjörg (Menntavísindasvið Háskóla Íslands, 2020)
This qualitative study focused on the daily lives, reflections and experiences of migrantfamilies (first generation) who had disabled children. Twelve families who had altogether16 disabled children participated in the study. The children were of age 2–17, seven werein preschool, eight in elementary or middle school and one in secondary school. Most ofthe children had autism spectrum disorder, often combined with intellectual impairmentor other health-related conditions. Five families were single-parent and seven twoparentfamilies of diverse countries of origin in Southern and Eastern Europe, CentralAmerica and Asia, with families from Eastern Europe in majority. Data were gatheredthrough semi-structured interviews and participant observations. The interviews wereconducted in Icelandic, English or with the help of a professional interpreter, in line withthe wishes of parents.The families in this study were not a homogeneous group with respect to language abilitiesand other characteristics. Some had lived in Iceland for a long time and had formedsocial networks either within their ethnic community or within the larger, Icelandicsociety. Other families did not have these networks. Comparison with the opportunitiesavailable in their country of origin was essential when people described their lives.Although parents talked about strenuous days, hard work and the struggle of combiningroles in employment with care of their children, most of them nevertheless appreciatedliving in Iceland, compared with what the situation would be in their country of origin.Parents received various types of social, educational and health services for theirchildren. In general, they were pleased with the services provided, particularly thosereceived during the preschool years. In contrast, the transition to elementary school wasoften demanding and, overall, parents of children of elementary and middle school ageheld more mixed views about their experiences of services. A range of barriers relatedto accessing information about their ...